ANALISIS KEGAGALAN INTERACTIVE GOVERNANCE DALAM TATA KELOLA RUANG TERBUKA PUBLIK OLEH PEMERINTAH KABUPATEN BOGOR DI KAWASAN PUNCAK BOGOR - Radhon Fayyadhsayya Albasith; Neny Marlina (Journal of Politic and Government Studies, 2026)
Public open space governance in the Puncak Area of Bogor continues to face various challenges, including the gap between regulatory frameworks and their implementation, weak coordination among government agencies, and limited public participation. This study aims to analyze the actor map and their relationships, as well as to identify the failure of implementing the principles of Interactive Governance in Simpang 4 Ciawi Park, Megamendung District Office Park, and Gunung Mas Rest Area. This research employed a descriptive qualitative approach using in-depth interviews, observations, and literature review, with data analyzed through the Miles and Huberman interactive model. The analytical framework was based on Jan Kooiman’s (2003) Interactive Governance theory, encompassing the dimensions of communication, coordination, negotiation, collaboration, and participation. The findings reveal that although the three public open spaces involve different actor configurations, they share similar governance problems, including hierarchical communication, weak inter-agency coordination, reactive negotiation, and suboptimal collaboration and public participation. The most significant governance failure occurred at Simpang 4 Ciawi Park, where the landowner was excluded from the planning process, resulting in the closure of the park. Meanwhile, the management of Megamendung District Office Park and Gunung Mas Rest Area continues to experience institutional and coordination challenges. The study concludes that the failure to implement the principles of Interactive Governance has prevented public open spaces from functioning optimally. Therefore, a more inclusive governance approach is required through stronger cross-sectoral coordination, meaningful public participation from the planning stage, and the establishment of post-development management standards.